PERKEMBANGAN KINERJA PERKUMPULAN PETANI PEMAKAI AIR DI KABUPATEN BANYUMAS(Studi Kasus Daerah Irigasi Andongbang, Banjaran, dan Tajum)DEVELOPMENT OF PERFORMANCE OF WATER USER FARMERS ORGANIZATION IN BANYUMAS REGENCY(Case Study of Irrigated Areas of Andongbang, Banjaran, and Tajum) - M., Hidayat; , Suroso (Pembangunan Pedesaan, 2005)
Government has given the real role to farmers, in Perkumpulan Petani Pemakai Air (P3A) organization, to manage irrigation systems agree with the existing rules. To know P3Aâs development achievement in Banyumas region, it was evaluated the achievement of three P3A, i.e : D.I Andongbang, D.I Banjaran, and D.I Tajum. The method of evaluation used was survey by using P3Aâs evaluation form with six (6) aspects, i.e: organization, water use, maintenance, financial, physical condition, and guideline. The result showed that the grade of P3A achievement of D.I Andongbang, D.I Banjaran, and D.I Tajum are 10,96 (54,8%), 10,77 (53,85%), and 15,83 (79,15%) with criteria poor, poor, and good respectively. And the level of their development P3A are developing, developing and developed respectively.